2014
DOI: 10.1016/j.ijms.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative electron attachment and dipolar dissociation in ethylene

Abstract: We present a detailed experimental investigation of anion production in electron collisions with ethylene, C 2 H 4 . The investigated energy range is between 0 and 90 eV where anions are formed by two processes, in the low energy regime by dissociative electron attachment (DEA) and at higher energy by dipolar dissociation (DD). These electron induced processes are studied in two different experimental apparatus using two different mass spectrometry techniques. One is a time of flight spectrometer operating wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…Above 15eV, the neglect of ionization and other significant open channels makes electron-polyatomic elastic scattering models of the SMC type less accurate and gives riseto disagreement between theory and experiment. At higher E 0 , agreement of the present experiment with those of Panajotovic et al[8] and of Mapstone and Newell[5] is very good to…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Above 15eV, the neglect of ionization and other significant open channels makes electron-polyatomic elastic scattering models of the SMC type less accurate and gives riseto disagreement between theory and experiment. At higher E 0 , agreement of the present experiment with those of Panajotovic et al[8] and of Mapstone and Newell[5] is very good to…”
supporting
confidence: 88%
“…Low energy DEA of ethylene, giving rise to Hanions, was recently measured by Cadez et al [4] who observed a weak, composite structure of 3 overlapping features at 7.5eV, 9eV and 10.7eV. More recently, the more detailed DEA measurements of Szymańska et al [5] confirmed this Hstructure, but in addition were also able to observe C -, CH - Electronically elastic scattering coupled to vibrational excitation of ethylene has also been previously studied, focused on resonant scattering involving electron attachment to the C=C and the C-H 2 bond systems. Elastic scattering measurements were made by Mapstone and Newell [6], Panajotovic et al [8], Khakoo et al [9] and by Allan et al [1].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…While this needs to corrected for stabilization of the ion, a shift of around 4 eV cannot be explained in this way, ruling out DEA to water as the initiating step in the reaction. DEA cross-sections to C 2 H 4 have also been reported, by Szymańska et al [24], but in much the same way as in water, no anion formation was observed below 6 eV. The only process that is known to occur is a non-dissociative electron attachment to water at around 1.5 eV.…”
Section: Prediction Of Possible Reaction Routessupporting
confidence: 70%
“…In this case we can exclude DEA from hydrocarbons present in the vacuum chamber since for these compounds resonances are only found at substantially higher electron energies. 51…”
Section: Ch 2 -mentioning
confidence: 99%